Family Therapy is Effective to Enhance Family Self-Sufficiency to Care For Elderly Family Members with Hypertension - Iskandar, Asep; Pratama, Koernia Nanda; Setiyani, Rahmi (Jurnal Keperawatan Soedirman, 2019)
Hypertension is a one of the most common medical problems affecting the elderly.Strategies to manage the problem is already developed. However, patient's compliance, particularly elderly, to follow hypertension management is considered low.Some factors contributed to patient's non-compliance behavior are including lack of motivation and family support. Lack of family support was associated to lack of family self-sufficiency for hypertension management.This study aimed at determines the effect of family therapy on family self-suffienciency in managing hypertension. This study used quasy experimental study with control group design.A total of 40 families which divided into two groups (treatment group and control group) were involved in this study.Samples in each group (20 families each) were assigned using simple random sampling technique. Level of family self-sufficiency was determined using Indonesian Ministry of Health definition. Data was analyzed using Wilcoxon test.Result showed that there was a significant difference in family self sufficiency level before and after intervention (p=0.000).Thus, it can be concluded that family therapy is effective to enhance family self-sufficiency to care for elderly family member with hypertension.